Flight performance and the factors affecting the flight behaviour of Philaenus spumarius the main vector of Xylella fastidiosa in Europe - Clara Lago (Nature Portfolio, 2021)
Abstract The recent emergence of Xylella fastidiosa in Europe is a major threat to agriculture, including olive, almond and grape. Philaenus spumarius is the predominant vector of X. fastidiosa in Europe. Understanding vector movement is critical for developing effective control measures against bacterial spread. In this study, our goal was to set up a flight-mill protocol to assess P. spumarius flight potential and to analyse how different variables may affect its flight behaviour. We found that P. spumarius was able to fly ≈ 500 m in 30 min with a maximum single flight of 5.5 km in 5.4 h. Based on the observations, the flight potential of the females was higher in spring and autumn than in summer, and that of the males was highest in autumn. Moreover, we found that P. spumarius had a higher flight potential during the morning and the night than during the afternoon. Our results revealed that P. spumarius is likely to disperse much further than the established sizes of the infected and buffer zones designated by the EU. This knowledge on the flight potential of P. spumarius will be critical for improving management actions against P. spumarius and the spread of X. fastidiosa in Europe.